RUKYATUL HILAL: KELAYAKAN TEMPAT OBSERVASI PANTAI BAROMBONG KOTA MAKASSAR - Yulia - Rahmadani; Famawati Hilal Hilal (Universitas Islam Negeri Alauddin Makassar, 2020)
The dating of Qamariyah is the date of Muslims in determining the entry and the feast of days, months, and years. In this dating system, it has a very close association with the setting of the sun which then the crescent (Hilal), then the observation process is done by this change, to know the entry of the beginning of the new month, this process is called Rukyatul Hilal. There are several techniques in the process of Rukyatul Hilal, so this process can be implemented. The success rate of the Rukyatul Hilal process is influenced by internal and external factors. One of the internal factors is related to weather conditions and the external factor of urgency is the location of the observation. Barombong Beach feasibility level as a place of Rukyatul Hilal can be measured based on geographical location and climatic conditions at the site. So, the means used to determine the level of feasibility of Barombong Beach as a place of Rukyatul Hilal can be data collected and also do a direct observation of the field research. With the condition of the western horizon that is free of all things that can obstruct the process of the pass and the weather condition are stable, then Barombong Beach is declared worthy as a place of Rukyatul Hilal. While keeping an eye on the existing systematics so there is no failure in the process of the Rukyatul Hilal.